ASSESSMENT OF THE CONDITIONS OF THE FARMING HOUSEHOLDS IN NORTH COTABATO: Using Comparative Analysis - Castillo, Rey; Datukan1, Amhed Jeoffrey J. (Applied Studies in Agribusiness and Commerce, 2023)
This study was conducted to assess the conditions of the farming households in North Cotabato as basis to reform the development of agri-preneurs in line with the country’s thrust of transforming farmers as entrepreneurs. The research analyzed the conditions of the farming households in North Cotabato in relation to the crops they produce. Stratified random sampling was employed in the collection of data from four hundred (400) farming households using a self-constructed questionnaire validated by the panel. Data generated were analyzed descriptively and by inferential statistics using analysis of Variance (ANOVA). The research revealed that the primary commodity produced is rice, followed by rubber and coconut. On the other hand, study revealed that respondents in the study are engaged in single farming, without Farming, and multiple farming. Among the perceived conditions of the farming households the study also revealed that conditions in terms of infrastructure facility, market information, managerial skills and entrepreneurial competencies are ready and available for the farmers but neither agree nor disagree on the availability of the conditions in terms of market opportunity, access to credit facility, enabling environment, and government policies on entrepreneurial development. The result affirmed the hypotheses that significant differences in the conditions of the farming household when analyzed according to the crops produced.